Curvature forms and Curvature functions for 2-manifolds with boundary - Eftekharinasab, K. (Інститут математики НАН України, 2009)
We obrain that any 2-form and any smooth function on a given 2-manifold with boundary can be realized as the curvature form and the gaussian curvature function of some Riemmanian metric, respectively.